The incidence, prevalence and clinical features of MECP2 duplication syndrome in Australian children. (12th February 2019) - Giudice‐Nairn, Peter; Downs, Jenny; Wong, Kingsley; Wilson, Dylan; Ta, Daniel; Gattas, Michael; Amor, David; Thompson, Elizabeth; Kirrali‐Borri, Cathy; Ellaway, Carolyn; Leonard, Helen
Abstract : Aim: The aim of this study was to assess the incidence and prevalence of MECP2 duplication syndrome in Australian children and further define its phenotype. Methods: The Australian Paediatric Surveillance Unit was used to identify children with MECP2 duplication syndrome between June 2014 and November 2017. Reporting clinicians were invited to complete a questionnaire. Clinician data ( n = 20) were supplemented with information from the International Rett Syndrome Phenotype Database and from caregivers ( n = 7). Birth prevalence and diagnostic incidence were calculated. Results: The birth prevalence of MECP2 duplication syndrome in Australia was 0.65/100 000 for all live births and 1/100 000 for males. Diagnostic incidence was 0.07/100 000 person‐years overall and 0.12/100 000 person‐years for males. The median age at diagnosis was 23.5 months (range 0 months–13 years). A history of pneumonia was documented in three quarters of the clinical cases, half of whom had more than nine episodes. Cardiovascular abnormalities were reported in three cases. A clinical vignette is presented for one child who died due to severe idiopathic pulmonary hypertension. The majority (13/15) of males had inherited the duplication from their mothers, and two had an unbalanced translocation. Conclusions: MECP2 duplication syndrome is a rare but important diagnosis in children because of the burden of respiratory illness and recurrence risk. Pulmonary hypertension is a rare life‐threatening complication. Array comparative genomic hybridisation testing is recommended for children with undiagnosed intellectual disability or global developmental delay. Early cardiac assessment and ongoing monitoring is recommended for MECP2 duplication syndrome.